Halotolerance and effect of salt on hydrophobicity in hydrocarbon-degrading bacteria. Issue 9 (2nd May 2016) - Longang, Adégilns; Buck, Chris; Kirkwood, Kathlyn M.
ABSTRACT: Hydrocarbon-contaminated environments often also experience co-contamination with elevated levels of salt. This paper investigates the occurrence of halotolerance among several hydrocarbon-degrading bacteria, as an initial assessment of the importance of salt contamination to bioremediation strategies. Halotolerance was common, but not ubiquitous, among the 12 hydrocarbon-degrading bacteria tested, with many strains growing at up to 75 or 100 g NaCl L −1 in rich medium. Greater sensitivity to elevated salt concentrations was observed among aromatics degraders compared to saturates degraders, and in defined medium compared to rich medium. Observed effects of high salt concentrations included increased lag times and decreased maximum growth. Many strains exhibited flocculation at elevated salt concentrations, but this did not correlate to any patterns in cell surface hydrophobicity, measured using the Bacterial Adhesion to Hydrocarbon assay. The occurrence of halotolerance in hydrocarbon-degrading bacteria suggests the potential for native microorganisms to contribute to the bioremediation of oil and salt co-contaminated sites, and indicates the need for a better understanding of the relationship between halotolerance and hydrocarbon biodegradation capabilities.